Legal Consequences Of Notary Deeds Signed By Parties Under The Influence Of Alcohol - Anang Shophan Tornado*; Nurunnisa Nurunnisa; Muhammad Fikri Azmi (JIM: Jurnal Ilmiah Mahasiswa Pendidikan Sejarah, 2023)
The notary has the authority to make authentic deeds and required to be professional, Article 1320 of the code of Civil law regulates the conditions for the validity of an agreement, one of which is subjective conditions is legal proficiency of the parties, but what if the notary lets one of the parties be under the influence of alcohol and make an authentic deed. So, the research aimed to find out how the status of the deed signed by the party who is under the influence of alcohol are and what are the legal consequences of a Notary who deliberately allows a party to be under the influence of alcohol. The result is that first, The deed becomes an underhanded deed and can then be cancelled because the condition influenced by the alcohol is not legally competent because the element of being able to perform legal acts is lost due to mental state, namely the lack of awareness of the party due to the influence of alcohol so that it does not fully use common sense when signing in the Notarial deed. Second, the notary may be subject to administrative sanctions in Article 85 of the Notary Law, namely verbal reprimand, written reprimand, temporary dismissal, honourable dismissal, or dishonourable dismissal. A notary can also be subject to civil or criminal sanctions if proven to have committed an unlawful act on the authentic deed that the notary has made.